Micromycetes associated with plants as biotechnology targets - Андріанова, Т. В.; Дражнікова, А. В.; Українська, А. О. (Problems of Environmental Biotechnology, 2019)
The review of modern research on microscopic fungi associated with plants and that are of interest for biotechnologies is presented. There are characterized the data on fungi of different taxonomic groups, which can exist asymptomatically in plant tissues and are considered endophytes, peculiarities of their biology and distribution. Approaches to their cultivation in vitro and the ability to synthesize a wide range of secondary metabolites are discussed. Some biologically active compounds derived from associated micromycetes have medicinal properties, as well as the ability to alter plant metabolism. The advantages and shortages of the application of these fungi as of biotechnology targets are outlined.